2000
DOI: 10.1002/1099-0682(200011)2000:11<2393::aid-ejic2393>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of the Phosphododecamolybdate Ion by Phosphonium Ylides and Phosphanes

Abstract: The reaction of phosphonium ylides with [PMo12O40]3− consists of successive single electron transfers leading to the formation of the 1e‐ and 2e‐reduced polyoxomolybdates [PMo12O40]4− and [PMo12O40]5−. The ylide is converted into the corresponding phosphonium cation via a radical‐cation intermediate. The reaction of phosphanes follows the same pathway but subsequent reactions with residual water produce protons which induce the disproportionation of [PMo12O40]4−. Authentic samples of heteropoly blues in differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 20 publications
2
9
0
Order By: Relevance
“…Meiklejohn et al [20] reported the same salt, obtained by chemical reduction as a 'dark green blue' product characterized only by analytical and spectroscopic data. Artero et al [21] isolated (PPh 4 ) 4 [PMo 12 O 40 ], the asolvate of the one electron reduced product we are reporting here, and stated that their product was blue-coloured. Characterization was limited to analytical, IR and UV-Vis data.…”
Section: Introductionsupporting
confidence: 50%
See 1 more Smart Citation
“…Meiklejohn et al [20] reported the same salt, obtained by chemical reduction as a 'dark green blue' product characterized only by analytical and spectroscopic data. Artero et al [21] isolated (PPh 4 ) 4 [PMo 12 O 40 ], the asolvate of the one electron reduced product we are reporting here, and stated that their product was blue-coloured. Characterization was limited to analytical, IR and UV-Vis data.…”
Section: Introductionsupporting
confidence: 50%
“…Two-and four-electron reduced anions with X = P have been structurally characterized [12,15]. One electron reduced species are very rare [16][17][18][19][20][21] and X-ray structure analysis is so far limited to the blue (Bu 4 N) 4 [PMo 12 O 40 ] Á 2DMF Á H 2 O, obtained by photochemical reduction [19] of the d 0 Keggin ion. Meiklejohn et al [20] reported the same salt, obtained by chemical reduction as a 'dark green blue' product characterized only by analytical and spectroscopic data.…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned above, the CVs of POMs in solution are strongly sensitive to the presence of small cations or protons and to their degree of association with the POM-reduced forms. 66,67,49 The behavior of Keggin anions in acidified aqueous, mixed aqueous/organic, and acetonitrile solutions has been extensively studied 68,62 and accounted for in terms of protonation of their reduced forms, according to their relative basicities. 50,51 For nonsubstituted POMs, one-electron, one-proton (or two-electron, two-proton) successive steps are generally considered.…”
Section: Cvs and Kinetic Analysis In The Presence Of A Largementioning
confidence: 99%
“…For polyoxometalates modified with amines, see ;. For the structures of other reduced heteropolyanions with composition [PMo 12 O 40 ] 4À , see: Artero & Proust (2000); Kurmoo et al (1998). ; Niu et al (1999).…”
Section: Related Literaturementioning
confidence: 99%
“…of a complex [Ni(C 8 Artero & Proust (2000); Kurmoo et al (1998);Niu et al (1999). The employed organic ligand appears to adjust the pH value, and additionally supplies reducing electrons, which is a commonly observed feature of hydrothermal syntheses when organic amines are used to prepare various hybrid materials, zeolites or metal phosphates (Yang et al, 2003).…”
Section: S1 Commentmentioning
confidence: 99%